PELAKSANAAN NEURO DEVELOPMENTAL TREATMENT (NDT) PADA CEREBRAL PALSY DIPLEGI TYPE SPASTIK DI PNTC KARANGANYAR - Wardani, Farra Kharisma; , Agus Widodo,S.Fis,M.Fis (2016)
Bacground: spastic cerebral palsy diplegi is the condition on the children who have movement disorders (paralisis) is caused by a non progressive brain injury or malformation that signified by tendon reflek development, the surplus stretch reflek, muscle hypercontractility, there is often clonus that occur on movement part which is the upper movement part is lighter than the lower movement part. Physioterapi modality that can use to handle the disturbance of movement and function of cerebral palsy is with NDT approach. Objective: to know the implementation of Practical Therapy Neurodevelopmental Treatment (NDT) in case spastic cerebral palsy diplegi toward to lowering spasticity level and the functional ability of standing and walking. Result: after implementing therapy for six times can be found that (1) spasticity level is constan on Asworth scale on the both legs of T1 to T6 can be found the constan marks is two. (2) the examination of functional movement by GMFM from T1 to T6 is found the constan mark is 42,68%. Conclusion: the implementation of practical Therapy Neuro Developmental Treatment (NDT) ) in case spastic cerebral palsy diplegi toward to lowering spasticity level and the functional ability of standing and walking indicating no change yet.